Pharmacogenomics and Pharmacogenetics: Some Cases in Oncology - Rika Yuliwulandari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTPharmacogenomics and pharmacogenetics plays an important role in understanding how genetic variants influence drug efficacy and toxicity. In the case of cancer, both efficacy and toxicity of therapeutic agents determine the improvement of survival and quality of life in cancer patients. Effective treatment of Cancer, one of the most deadly diseases in the world, is importance for extending patient survival. Genetic variation influences the response of an individual to drug treatments that impact the efficacy and toxicity of the drugs. Understanding individual genetic variation is potential to make therapy safer and more effective by determining more appropriate drug selection and drug dosage for each individual patient. In the context of cancer, tumors may have specific disease-defining mutations, but a patient’s germline genetic variation will also affect drug response. Advance research technologies approach such as GWAS and next-generation sequencing technologies, statistical genetics analysis methods and clinical trial design have shown promise for discovery of genetic variants associated with drug response in cancer. Understanding the molecular characteristics of both the tumor and the patient, and establishing their relation with drug outcomes will be critical for the identification of predictive biomarkers and to provide the basis for individualized treatments. Since cancer is also frequent in Indonesia, pharmacogenomics study in oncology and its implementation in the clinical practice is important. Broad collaboration at national and international level could foster the application of personalized medicine in oncology.